Pemetaan Stakeholder dalam Rencana Tata Tanam Global Berbasis Neraca Air Irigasi - Oktaviano Oktaviano; Efrilia Efrilia; Ali Sadikin (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Stakeholder mapping is not merely an auxiliary communication activity in irrigation planning; it is a governance instrument that determines whether technical water-balance calculations can be converted into legitimate cropping schedules, coordinated operations, and collective compliance at the field level. This study analyzes the configuration of stakeholders in the implementation of a water-balance-based Global Cropping Plan (RTTG) in Musi Rawas Regency, Indonesia. A descriptive qualitative case-study approach was employed. Data were collected through field observation, in-depth interviews, and focus group discussions involving local government agencies, planning and technical departments, irrigation officers, agricultural extension workers, farmer water-user associations, farmer groups, rice farmers, fish farmers, and community water users. The data were processed through thematic coding, role identification, triangulation, and a power-interest matrix. The findings indicate that RTTG implementation depends on the alignment of four actor clusters: policy steering actors, technical-operational actors, regulatory and resource-support actors, and water users. Promoters with high power and high interest must be engaged intensively as policy legitimators and coordination drivers; latents must be approached through legal, budgetary, and institutional arguments; defenders require participatory empowerment as field implementers and social monitors; and apathetics need concise public information to prevent misinformation. The study concludes that stakeholder mapping strengthens adaptive irrigation governance by integrating technical data, institutional authority, farmer participation, and food-security objectives.